Effect of Perforation Interval Design on Gas Production from the Validated Hydrate-Bearing Deposits with Layered Heterogeneity by Depressurization - Yingli Xia; Tianfu Xu; Yilong Yuan; Xin Xin (Geofluids)
Natural gas hydrate is considered as one of the best potential alternative resource to address the world’s energy demand. The available geological data at the Mallik site of Canada indicates the vertical heterogeneities of hydrate reservoir petrophysical properties. According to the logging data and sample analysis results at the Mallik 2L-38 well, a 2D model of geologically descriptive hydrate-bearing sediments was established to investigate the multiphase flow behaviors in hydrate reservoir induced by gas recovery and the effects of perforation interval on gas production performance. Firstly, the constructed model with vertical heterogeneous structures of permeability, porosity, and hydrate saturation was validated by matching the measured data in the Mallik 2007 test. The excessive residual methane in the hydrate reservoir observed in simulated results indicates insufficient gas production efficiency. For more effective methane recovery from a hydrate reservoir, the effect of perforation interval on long-term gas production performance was investigated based on the validated reservoir model. The simulation results suggest that both the location and length of the perforation interval have significant impact on hydrate dissociation behavior, while the gas production performance is mainly affected by the length of the perforation interval. To be specific, an excellent gas release performance is found in situations where the perforation interval is set at the interface between a hydrate reservoir and an underlying water-saturated zone. By increasing the perforation interval lengths of 5 m, 8 m, and 10 m, the gas release volumes from hydrate dissociation and gas production volumes from production wells are increased by 34%, 52%, and 57% and 37%, 58%, and 62%, respectively.